2019
DOI: 10.3390/gidisord1020022
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacteria and Mucosal-Associated Invariant T (MAIT) Cells: A New Approach to Colorectal Cancer Prevention?

Abstract: Colorectal cancer is the most preventable form of cancer worldwide. The pathogenesis of colorectal cancer includes gut inflammation, genetic and microbial composition factors. İmpairment of the gut microbiota has been associated with development of colorectal cancer. The genus Bifidobacterium is an important component of the commensal gut microbiota. Bifidobacteria are considered to have important roles in multiple homeostatic functions: immunologic, hormonal and metabolic. Mucosal-associated invariant T cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 50 publications
0
13
0
2
Order By: Relevance
“…However, since immunological mechanisms play an important role in the course of the disease, a novel therapeutic approach involving probiotic bacterial strains might be promising because of their involvement in immune modulation [120,204,210]. In this regard, interleukin-17 is a pro-inflammatory cytokine with a crucial role in the adaptive immune system, and it is also a potent inducer of endoplasmic reticulum stress autophagy through inositol-requiring enzyme 1 [17,88]. By blocking this interleukin, autophagy mediated by endoplasmic reticulum stress and inflammation can be prevented [60,88].…”
Section: The Potential Effects Of Probiotics On Coronavirus Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since immunological mechanisms play an important role in the course of the disease, a novel therapeutic approach involving probiotic bacterial strains might be promising because of their involvement in immune modulation [120,204,210]. In this regard, interleukin-17 is a pro-inflammatory cytokine with a crucial role in the adaptive immune system, and it is also a potent inducer of endoplasmic reticulum stress autophagy through inositol-requiring enzyme 1 [17,88]. By blocking this interleukin, autophagy mediated by endoplasmic reticulum stress and inflammation can be prevented [60,88].…”
Section: The Potential Effects Of Probiotics On Coronavirus Infectionmentioning
confidence: 99%
“…By blocking this interleukin, autophagy mediated by endoplasmic reticulum stress and inflammation can be prevented [60,88]. Interestingly, Bifidobacterium strains have an inhibitory effect on interleukin-17 [17]. Consequently, administration of high doses of Bifidobacterium strains such as B. animalis subsp.…”
Section: The Potential Effects Of Probiotics On Coronavirus Infectionmentioning
confidence: 99%
“…A brief report 39 claimed that high-single dose endoscopic administration of appropriate and reliableBifidobacterium Infantis (BB-12 ), as potential probiotic, or use of these strains' lipopolysaccharide membranes in vaccine development especially in patients with gastrointestinal symptoms (diarrhea, abdomen pain, vomiting) can result in more therapeutic and preventive effects in Coronavirus-infected patients 40,41 . Consequently, Bifidobacterium animalistheoretically can inhibit the replication of coronaviruses by reducing ER stress-related autophagy, especially the inositol-requiring enzyme 1 (IRE1) pathway, over its anti interleukin-17 effect 19 . Apparently, the main pathogenic mechanism that makes viral infection-induced pneumonia seems to be a "cytokine storm"; IL-6 is the main proinflammatory marker in this regard 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Oral Lactobacillus casei ATCC 39392 vaccine polarized Th2 cell immunity and stimulated IL-17 expression against transmissible gastroenteritis coronavirus (TGEV) 18 , however, an anti interleukin (IL)-17 effect was observed for Bifidobacterium animalis 19 . In another study, the probiotic strain "heat-killed Lactobacillus plantarum L-137 " was introduced as an IL-12 inducer in mice 20 .…”
Section: Effects On Level Of Interleukinsmentioning
confidence: 99%
“…Lactis-BB12 led to rapid mucosal healing in an ulcerative colitis patient. 7,19 This effect was related to the IL-17 inhibitory effect of the BB-12 strain. Zuo et al 20 showed that patients with COVID-19 had a significantly disrupted gut microbiome, characterised by enrichment of opportunistic pathogens and depletion of beneficial commensal bacteria.…”
Section: Bifidobacteria In the Management Of Covid-19mentioning
confidence: 95%